The Polish model of civil post-conviction preventive detention in the light of the European Convention on Human Rights. Issue 10 (26th November 2021) - Szwed, Marcin
ABSTRACT: The article presents an overview of the Polish model of post-conviction preventive detention (PPD) and analyses its compatibility with the European Convention on Human Rights. PPD is defined as detention of offenders who present a high re-offending risk, which may be applied for an unspecified period after the conclusion of an offender's prison sentence for preventive reasons. Until 2013 the Polish system of PPD was relatively limited. However, in 2013, in the atmosphere of moral panic aroused by the media in the context of the expected release of dangerous offenders sentenced to a death penalty under communism and saved by the 1989 amnesty law, the Parliament adopted a law which significantly extended it. The new law allowed on placement of offenders, after completion of their sentence, in the allegedly therapeutic centre. The law raised serious controversies among legal scholars and psychiatrists, however in 2016 the Constitutional Tribunal ruled that, for the most part, it was consistent with the Constitution. The article argues that the system of detention established in the 2013 law violates the ECHR. That is caused not only by the flawed legal regulations but also practical problems resulting, among others, from unexpectedly high influx of new detainees.